Ekstraksi Oleoresin Dari Jahe Emprit (Zingiber Officinale var. Amarum) Dengan Metode Sokletasi - Naidir, Ferra; Retno Wulandari; Pandit Hernowo; Andi Nuraliyah; Agung Siswahyu; Tulus Sukreni; Lisa Adhani (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Indonesia produces many useful spice plants, included ginger (zingiber officinale). Ginger is extracted to produce oleoresin, active components, such as gingerol, shogaol, and zingiberene, providing a distinctive aroma and taste usefully for the food, pharmaceutical, and cosmetic industries. The study obtain the best value on the variable size of ginger powder and the duration of soaking in solvent (96% ethanol) on oleoresin yield, using the soxhlet extraction method. The ratio of ginger powder and ethanol is 1: 10 (w / v) with ginger powder sizes of 20, 40, 60 mesh and soaking times of 0, 3, 9 hours, operated at a temperature of 70 ° C for 90 minutes. The process ends with simple distillation at a temperature between 66 - 69 oC for 90 minutes to purify the ginger oleoresin from the solvent. The highest yield of 88%, weighed 19.262 grams, was obtained from 60 mesh (0.250 mm) ginger powder with a soaking time of 9 hours. The average oleoresin SG value is 0.88-0.98 gr/mL with a refractive index of 1.03-1.07. From the chromatogram of the GC-MS analysis results, it was known that the highest active component was zingiberene at 26.43% which was obtained at 20.48 minutes.